2020
DOI: 10.3390/cancers12113228
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Beta-Adrenergic Blocking Agents in Cutaneous Melanoma—A Nation-Wide Swedish Population-Based Retrospective Register Study

Abstract: Previous studies have demonstrated an anti-tumoral effect of beta-adrenergic blocking agents on cutaneous melanoma (CM). The aim of this study was to investigate if beta-adrenergic blocking agents have an impact on survival in Swedish patients with melanoma. A population-based retrospective registry study including all patients diagnosed with a primary invasive melanoma between 2009 and 2013 was performed. Data from the Swedish Melanoma Register were linked to the Swedish Prescribed Drug Registry and the Swedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…Lemeshow et al Katsarelias et al 38 The effect of βadrenergic blocking agents in cutaneous melanoma-a nation-wide Swedish population-based retrospective register study…”
Section: Noof Participants Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lemeshow et al Katsarelias et al 38 The effect of βadrenergic blocking agents in cutaneous melanoma-a nation-wide Swedish population-based retrospective register study…”
Section: Noof Participants Resultsmentioning
confidence: 99%
“…Thus, they concluded that βblocker use was not associated with reduced risk of death from melanoma. 37 Katsarelias et al 38 investigated the effects of βblockers in cutaneous melanoma. Of 12,738 patients, 3702 received βblockers, and 9036 did not.…”
Section: 378mentioning
confidence: 99%
See 1 more Smart Citation
“…We read the paper by Katsarelias et al with great interest, regarding the effect of beta-adrenergic blocking agents on cutaneous melanoma [ 1 ]. However, the study presents some methodology biases that do not allow us to support the authors’ conclusions.…”
mentioning
confidence: 99%
“…As a general comment, the idea of a positive effect of beta-blockers in reducing recurrence of melanoma is very intriguing [ 1 , 2 ], and therefore our aim was to investigate this in a large cohort of patients. The study was a retrospective registry-based study including 12,738 patients with melanoma, where 3702 were exposed to beta-blockers [ 3 ].…”
mentioning
confidence: 99%